Assessment of air pollution level in Sonbhadra district using air quality index - Himanshu Shekher; Sushil Kumar Yadav; Pankaj Kumar Yadav; Shalini Tiwari; Kaushalendra Prakash Goswami (National Geographical Journal of India, 2023)
Air pollution constitutes the most significant issue affecting India. A multitude of individuals are experiencing various ailments as a direct consequence of air pollution. The Air Quality Index (AQI) is employed as a means to report the state of air pollution, providing a daily assessment of air quality. The examination of air quality serves the purpose of assessing the atmospheric condition in a given location. To facilitate this, the Central Pollution Control Board (CPCB) has established monitoring centers in two areas within the Sonbhadra district, namely Annpara colony and Renusagar colony. A comprehensive investigation spanning six years (2017-2022) has been conducted for the Sonbhadra district, examining the annual and seasonal fluctuations in the Air Quality Index. The data utilized for this analysis was obtained from CPCB and enabled the calculation of annual figures by determining the average mean. Moreover, the pollution situation in the city was evaluated using the exceedance factor (EF). The examination of these figures reveals that the city exhibits a higher concentration of PM 10 pollutants. Conversely, the levels of NO2 and SO2 are relatively well-regulated. Notably, the year 2018 was marked by the highest levels of pollution, while 2020 witnessed the lowest pollution levels. These findings suggest that the pollution prevention measures implemented in the city over the years have been effective.